Was it worth it? Infertile couples’ experience of assisted reproductive treatment and psychosocial adjustment one year after treatment - Moura-Ramos, Mariana (2018)
Undergoing Assisted Reproductive Technology (ART) can be a demanding experience. We aimed to describe changes in psychosocial adjustment from ART treatment to one year after and couples’ evaluation of the treatment’s experience. The study used a longitudinal design, with 33 infertile couples who were assessed during their ART treatment and one year after treatment regarding their emotional reactivity, emotional distress and quality of life; additionally, participants were asked to evaluate their treatment experience. Results indicated that from the ART cycle to one year after, couples who have achieved pregnancy showed an increase in positive emotions and a decrease in negative emotions. However, all couples evaluated the experience of ART in a positive way, regardless of treatment outcome, although more positive ratings were found in couples who have achieved pregnancy. It can be concluded that the emotional reactivity and the evaluation of the experience one year after treatment is affected by the treatment outcome.